Belarus Agricultural Productivity and Competitiveness : Impact of State Support and Market Intervention - World Bank (Washington, DC, 2014)
Productivity in Belarus' agricultural sector has improved considerably, but large parts of crop and livestock production are not internationally competitive. The state's regulatory and fiscal support system for agriculture has been instrumental in improving the sector's performance. But the massive distortions to agricultural incentives it creates to prevent the sector from reaching its full potential. And the high costs it causes to state budget may be difficult to sustain in view if shrinking fiscal space. Agricultural sector efficiency and competitiveness in Belarus can be increased by re-orienting the sectoral policy framework towards less distortive measures and reallocating associated budget expenditures to support sustainable agricultural growth. Assistance program could be provided to buffer against structural adjustment shocks. The government will thus achieve its sectoral goals to a higher degree, without compromising on other important policy areas such as food security and rural livelihoods, and possibly even at lower cost to the state budget. This note provides an economic justification for such reforms and outlines some potential elements.